Preliminary evaluation of 18F-FDG-PET/MRI for differentiation of serous from nonserous pancreatic cystic neoplasms: a pilot study. Issue 12 (December 2020) - Sagheb, Soodeh; Metser, Ur; Razaz, Suzan; Menezes, Ravi; Gallinger, Steven; Jhaveri, Kartik S.
Abstract : Objectives: The aim of the study was to evaluate preliminary feasibility of 18F-FDG-PET/MRI in differentiation of pancreatic serous cystic neoplasms (SCNs) from non-SCNs. Methods: From August 2017 to June 2019, 10 patients (3 men, 7 women; mean age, 63 years) previously diagnosed with pancreatic cystic neoplasm underwent simultaneous 18F-FDG-PET/MRI prospectively on an integrated 3-Tesla hybrid PET/MRI scanner. PET images were analyzed visually and semiquantitatively measuring standardized uptake values (SUV) including lesion SUVmax and SUVmean, lesion to pancreas and lesion to liver SUVmax and SUVmean ratio independent of MRI diagnosis. The reference standard for lesion diagnosis was by MRI features and interval follow-up. Results: Visual assessment of PET images demonstrated uptake in 57% of SCNs. Lesion to liver SUVmax ratio of ≥0.5 showed the highest accuracy (90%) and area under the curve (0.9) followed by lesion SUVmax of ≥1.6 and lesion to pancreas SUVmax ratio of ≥0.77 for diagnosis of SCN. The sensitivity for lesion SUVmax of ≥1.6 was less than two other ones (71 versus 100%). All non-SCNs exhibited SUVmax value less than 1.6 while 33 and 66% demonstrated lesion to liver SUVmax ratio of >0.5 and lesion to pancreas SUVmax ratio of >0.77, respectively. PET/MRI specificity was 67, 100, 67 and 33% through lesion to liver SUVmax ratio, lesion SUVmax, lesion SUVmean and lesion to pancreas SUVmax ratio, respectively, for diagnosis of SCN. Conclusion: Preliminary results show that PET/MRI utilization is promising for differentiation of pancreatic SCN from non-SCN lesions. This could reduce need for surveillance imaging or avoidance of unnecessary intervention in pancreatic cystic neoplasms with uncertain diagnoses.